Synthesis of chitosan-based polymeric dyes as colorimetric pH-sensing materials: Potential for food and biomedical applications - Chalitangkoon, Jongjit; Monvisade, Pathavuth (My University, 2021)
pH-sensitive polymeric dyes were fabricated by grafting phenol red (PR) and rosolic acid (RA) onto chitosan (CS) by a facile method. Successful grafting was confirmed by 1H NMR, FT-IR, UV–vis, XRD, and elemental analysis. The polymeric dyes exhibited no cell toxicity. The colorimetric pH-sensing films were fabricated by blending the polymeric dyes with CS to establish their pH-dependent color properties. The film color changed in the pH range 4–10, which may indicate food spoilage or wound status. Covalently grafting of polymeric dyes in the films led to excellent color stability, leaching resistance, and reversibility. Hence, the synthesized polymeric dyes had potential as pH-indicative colorants for food and biomedical fields.
Keywords: Chitosan; pH-sensing materials; Phenol red; Polymeric dye; Rosolic acid